2019
DOI: 10.1038/s41598-019-43315-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the trabecular meshwork length between open and closed angle with evaluation of the scleral spur location

Abstract: This study analysed the trabecular meshwork (TM) length in open and closed angle patients and presented a better method for locating the scleral spur using Schwalbe’s line method in anterior segment optical coherence tomography (AS-OCT). Patients who underwent AS-OCT at Yonsei University Gangnam Severance Hospital we enrolled; 58 and 57 open and closed angle eyes, respectively. We measured the distance from the scleral spur to Schwalbe’s line as the TM length and compared it between open and closed angle patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In the present study, our goal was to evaluate the previously suggested theory that there might be an association between the prevalence of glaucoma and TM length by comparing TM lengths of a South Korean population with those of other ethnic populations. Based on previous studies that have reported differences in TM length between open- and closed-angle patients, we compensated the TM length data of the South Korean patients with the corresponding open- and closed-angle ratios of each ethnic group in the previously discussed American study for a more accurate comparison [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, our goal was to evaluate the previously suggested theory that there might be an association between the prevalence of glaucoma and TM length by comparing TM lengths of a South Korean population with those of other ethnic populations. Based on previous studies that have reported differences in TM length between open- and closed-angle patients, we compensated the TM length data of the South Korean patients with the corresponding open- and closed-angle ratios of each ethnic group in the previously discussed American study for a more accurate comparison [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that anterior chamber depth is affected by race and ethnicity, and since AXL, ACD, and spherical equivalents are all closely related to each other, it can be assumed that TM length will be influenced by these factors [ 12 , 20 , 21 , 22 ]. It is also widely discussed about the prevalence of glaucoma (especially angle closure glaucoma) associated with different ethnicities with different angular parameters, including AXL, ACD, and spherical equivalents [ 7 , 8 , 18 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we randomly selected adult patients with open anterior chamber angle and compared their TM heights after categorising them into their age groups to indirectly evaluate possible changes in TM height. Because there is a known difference between the open angle and closed angle TM heights, for a more accurate comparison, we excluded patients with closed angles and performed the study only on patients with open angles 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Standard protocols for TM height measurement that have been described previously were used 6 . Briefly, TM height was measured in the nasal and temporal sides of the eye using AS-OCT by manually selecting the 3 and 9 o' clock positions as the nasal and temporal positions, respectively.…”
Section: As-oct Measurements All Patients Included In This Study Undmentioning
confidence: 99%